INCREASING KNOWLEDGE OF FISH PROCESSING THROUGH TRAINING ON MAKING FISH-BASED CULINARY PRODUCTS - Aisyahra, Elfina Agung; Ratnaningsih, Nani (Home Economics Journal, 2025)
This research aims to determine the level of knowledge about fish processing among women entrepreneurs before receiving training on fish-based culinary product making, describe the implementation of the training, measure the level of knowledge after the training, and identify changes in knowledge among women entrepreneurs in Sardonoharjo Village, Ngaglik, Sleman. This study employs a quantitative descriptive approach with a one-group pretest–posttest quasi-experimental design. The population consists of women who are culinary MSME entrepreneurs in Sardonoharjo Village, and all 118 participants were selected using a total sampling method. The research instrument was a 31-item knowledge test that had been previously validated and tested for reliability. Data were analysed using descriptive statistics, the N-gain test, and the paired sample t-test. The findings indicate that the participants’ knowledge of fish processing before the training was at a moderate level, with an average pretest score of 10.38, and the lowest performance was observed in the C3 and conceptual domains. The training was delivered through a lecture method combining theoretical material about fish with practical processing activities. After the training, the participants’ knowledge remained in the moderate category. Still, it improved substantially, with an average post-test score of 22.71, and the most significant increase occurred in the C2 and conceptual domains. Overall, there was a significant improvement in knowledge, reflected by an N-gain score of 0.63, indicating a moderate level of effectiveness of the fish-based culinary training program.